Application of Art Therapy for Coping with Post-Traumatic Stress Disorder: Future Directions" - Волотовська, Наталія (Psychosomatic Medicine and General Practice, 2023)
There is an increasing recognition in the social space of the need to safeguard mental health and pay attention to one’s emotional well-being. Concepts like emotional intelligence are no longer the exclusive domain of psychology professionals, as students and even schoolchildren today familiarize themselves with these ideas. Medical practitioners, both in therapeutic and surgical fields, are also focusing on emotional disturbances resulting from acute systemic or chronic illnesses. Examples of such pathologies include post-traumatic stress disorder following massive military trauma or emotional lability induced by hyperthyroidism. Furthermore, even elderly individuals are rediscovering creative activities that once brought them pleasure. All these are examples of how to care for one’s mental health. Although the pathogenetic processes triggering changes in mental activity are diverse, understanding the primary cause-and-effect relationship and the reciprocal influence of the cerebral cortex on stabilizing one’s state are undeniable. Hence, research into methods of influencing the cerebral cortex and discovering techniques capable of stabilizing psycho-emotional lability is vital and relevant.